Blind users' assistive technology based on the Android platform. (2017) - Al-Nabulsi, Jamal; Ma'touq, Jumana; Abdallah, Emad E.; Haloubi, Tarek; Manasra, Ali
Because of the wide use of smartphones in our daily activities, a wide range of mobile applications have been developed to serve as assistive technologies. However, there is a lack of applications in the Arabic language to assist disabled people. The main aim of this paper is to build a simple yet accurate Arabic language application that is capable of helping blind users in real-time. In the proposed technology, the blind user captures a photo and records his/her voice inquiry. The query is instantly sent with the captured photo to a set of volunteers. The volunteers answer the blind user enquiries and send the answers back. Fifteen visually impaired persons and ten volunteers were used in the experimental testing. The scenarios were carefully created based on realistic situations. The subjects were then asked to answer a questionnaire to test if their queries were answered effectively and efficiently. The early results are promising because all blind users found the proposed technology useful and 80% of them wanted to use it on a daily basis. In addition, all volunteers found the application easy to use with clear instructions and 80% of them were excited about using it to assist blind users.